Containing COVID-19 in China: AI and the robotic restructuring of future cities. Issue 2 (July 2020) - Chen, Bei; Marvin, Simon; While, Aidan
COVID-19 has generated interest in the potential of urban robotics and automation to manage and police physical distancing and quarantine. This commentary examines the intersection between COVID-19 management strategies and the technological affordances of robotics, autonomous systems, and artificial intelligence (AI) in urban pandemic control. Examples from China illustrate the possibilities for urban robotics and automation in a new era of urban bio-(in)security.